Pendidikan Literasi Keuangan untuk Masyarakat - Putra, Zetra Hainul; Al Firdaus, Miftahul Haqie; Rofiqa, Syavia; Fariq, Muhammad Adzin; Djamilah, Masyitoh; Novyanti, Novyanti; Geraldin, Hanes; Fernelia, Tiara; Tupamahu, Febiyanti; Febriananda, Putri; Apriani, Syelly (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Financial knowledge is needed as a factor in changing mindsets in managing finances well. Various methods are needed to help understanding and knowledge about financial management, one of which is financial literacy in schools which makes this teaching as a balance and complement to the financial education that children have received from their parents, besides that it can also make financial literacy as a control system in think children in managing money well and correctly. The purpose of financial literacy is to provide a broad understanding to students in school about a good financial management system. The methods used are in the form of providing material to students through the OJK book on the benefits of saving and providing an introduction to safe and practical savings in banks as a basic effort of financial literacy science and demonstrating the implementation of good financial management through videos as an effort explore the treatment and behavior in the financial control system in everyday life.